“Prevalencia de anomalías dentarias de forma y su asociación con la caries de infancia temprana” - Liliana Patricia, Saltos Viteri (2020)
The objective of this research was to identify the prevalence of shape dental anomalies in clinical records of 28 Child Development Centers (CDI) in Riobamba city and establish their relationship with early childhood caries. The medical records correspond to children of an age range of 0 to 3 years. The study population was 834 medical records, only 34 were corresponded to non-probabilistic intentional sample. The study was observational, descriptive, transversal and retrospective. The technique was the observation and the instrument; the checklist. The information analyzed in the medical record corresponded to the years 2015-2018. The results of the study indicated a prevalence of fusion and budding of 3.8% and 0.02% respectively. Similarly, the prevalence of early childhood caries was 9% and no significant difference was found with sex and age. As a general conclusion of the study, it was possible to determine the frequency of shape dental anomalies are not related to early childhood caries, the distribution of values of the ceod index for both budding and fusion was the same among patients therefore there was not found significant differences. (p = 0.602).